2016
DOI: 10.1016/j.neuroimage.2015.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and reliability of automatically segmented human hippocampal formation subregions

Abstract: The human hippocampal formation can be divided into a set of cytoarchitecturally and functionally distinct subregions, involved in different aspects of memory formation. Neuroanatomical disruptions within these subregions are associated with several debilitating brain disorders including Alzheimer’s disease, major depression, schizophrenia, and bipolar disorder. Multi-center brain imaging consortia, such as the Enhancing Neuro Imaging Genetics through Meta-Analysis (ENIGMA) consortium, are interested in studyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
122
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(136 citation statements)
references
References 79 publications
14
122
0
Order By: Relevance
“…Subcortical structures are also heterogeneous and consist of functionally diverging sub-regions, such as the nuclei of the pallidum or the head and tail of the caudate. Our results are in line with a recent study by Whelan et al 24. showing that hippocampal subfields differ in their heritability.…”
Section: Discussionsupporting
confidence: 94%
“…Subcortical structures are also heterogeneous and consist of functionally diverging sub-regions, such as the nuclei of the pallidum or the head and tail of the caudate. Our results are in line with a recent study by Whelan et al 24. showing that hippocampal subfields differ in their heritability.…”
Section: Discussionsupporting
confidence: 94%
“…The heritability estimates for HF subregions observed in this study, based on Human Connectome Project (HPC), closely resemble those recently reported based on the Queensland Twins Imaging Study (QTIM): heritability for all regions, except the fimbria differed by less than 0.10 (25). One interpretation of our findings is that almost all hippocampal subfields are substantially heritable.…”
Section: Discussionsupporting
confidence: 85%
“…We have previously analyzed FreeSurfer v6.0 output from different scanners with evidence that scanner heterogeneity provides robust and consistent results for hippocampal segmentation [4] and hippocampal subfield segmentation [25]. …”
Section: Discussionmentioning
confidence: 99%